2017
DOI: 10.1080/13510002.2017.1418191
|View full text |Cite
|
Sign up to set email alerts
|

Exercise through a cardiac rehabilitation program attenuates oxidative stress in patients submitted to coronary artery bypass grafting

Abstract: The results suggest that regular exercise through a cardiac rehabilitation program can attenuate oxidative stress in chronic coronary artery disease patients submitted to coronary artery bypass grafting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…It was shown that lipid and protein oxidation in erythrocyte membrane leads to an increase in their mobility [ 41 ]. The results of our study are consistent with those of Taty Zau et al [ 42 ], which demonstrate a decrease in thiobarbituric acid reactive substances (TBARSs) and carbonyl levels after CCR. It seems that changes in lipid fluidity are rather associated with alterations in protein-lipid interaction.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It was shown that lipid and protein oxidation in erythrocyte membrane leads to an increase in their mobility [ 41 ]. The results of our study are consistent with those of Taty Zau et al [ 42 ], which demonstrate a decrease in thiobarbituric acid reactive substances (TBARSs) and carbonyl levels after CCR. It seems that changes in lipid fluidity are rather associated with alterations in protein-lipid interaction.…”
Section: Discussionsupporting
confidence: 93%
“…Generally, CCR attenuates oxidative stress in CAD patients [ 42 ]. It has been established in this study that the rehabilitation training led to a reduction in oxidative stress indicators such as malonyldialdehyde and carbonyl compounds, as well as an increase in total antioxidant capacity including glutathione in patients after CCR [ 42 ]. Additionally, an increase in the enzyme activities of antioxidants such as SOD-1, GSH-Px, and catalase was demonstrated [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Instead, a higher CVR to an acute bout of exercise could be due to the influence of physical activity and walking on vascular health by reducing oxidative stress and increasing vasomotor reactivity. [28][29][30][31] Previous work reported that an 8-week physical activity intervention during subacute stroke reduced oxidative stress 32 and a 6-month walking intervention in chronic stroke increased the ability of the cerebrovascular system to vasodilate and vasoconstrict. 31 Our previous work has shown that self-reported physical activity at 3 and 6 months poststroke was associated with a greater CVR than those reporting low physical activity levels.…”
Section: Cerebrovascular Responsementioning
confidence: 99%
“…Several studies have shown the utility of exercise training and cardiac rehabilitation in the management of HF and coronary artery disease. 63 64 65 Cardiac rehabilitation was designed to formulate exercise training for postmyocardial infarction patients to help with recovery and self-care. 66 The United States Center for Medicare Services recently decided to extend cardiac rehabilitation coverage to HFrEF patients as several studies showed the benefits of exercise training to improve HFrEF clinical outcomes.…”
Section: Managementmentioning
confidence: 99%